mmt-007-solved-assignment-2024-ss-020cab3d-1c01-486f-9bdf-7506d86b97ee
a) Show that
f
(
x
,
y
)
=
x
y
f
(
x
,
y
)
=
x
y
f(x,y)=xy f(x, y)=x y f ( x , y ) = x y
i) satisfies a Lipschitz condition on any rectangle
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
c
≤
y
≤
d
c
≤
y
≤
d
c <= y <= d c \leq y \leq d c ≤ y ≤ d ;
ii) satisfies a Lipschitz condition on any strip
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
−
∞
<
y
<
∞
−
∞
<
y
<
∞
-oo < y < oo -\infty<y<\infty − ∞ < y < ∞ ;
iii) does not satisfy a Lipschitz condition on the entire plane.
Answer:
To show that the function
f
(
x
,
y
)
=
x
y
f
(
x
,
y
)
=
x
y
f(x,y)=xy f(x, y) = xy f ( x , y ) = x y satisfies a Lipschitz condition on certain domains, we need to find a constant
L
L
L L L such that for all points
(
x
1
,
y
1
)
(
x
1
,
y
1
)
(x_(1),y_(1)) (x_1, y_1) ( x 1 , y 1 ) and
(
x
2
,
y
2
)
(
x
2
,
y
2
)
(x_(2),y_(2)) (x_2, y_2) ( x 2 , y 2 ) in the domain,
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
≤
L
(
x
1
−
x
2
)
2
+
(
y
1
−
y
2
)
2
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
≤
L
(
x
1
−
x
2
)
2
+
(
y
1
−
y
2
)
2
|f(x_(1),y_(1))-f(x_(2),y_(2))| <= Lsqrt((x_(1)-x_(2))^(2)+(y_(1)-y_(2))^(2)) |f(x_1, y_1) – f(x_2, y_2)| \leq L\sqrt{(x_1 – x_2)^2 + (y_1 – y_2)^2} | f ( x 1 , y 1 ) − f ( x 2 , y 2 ) | ≤ L ( x 1 − x 2 ) 2 + ( y 1 − y 2 ) 2
i)
On a rectangle
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
c
≤
y
≤
d
c
≤
y
≤
d
c <= y <= d c \leq y \leq d c ≤ y ≤ d :
Consider any two points
(
x
1
,
y
1
)
(
x
1
,
y
1
)
(x_(1),y_(1)) (x_1, y_1) ( x 1 , y 1 ) and
(
x
2
,
y
2
)
(
x
2
,
y
2
)
(x_(2),y_(2)) (x_2, y_2) ( x 2 , y 2 ) in the rectangle. Then,
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
=
|
x
1
y
1
−
x
2
y
2
|
=
|
x
1
y
1
−
x
1
y
2
+
x
1
y
2
−
x
2
y
2
|
≤
|
x
1
|
|
y
1
−
y
2
|
+
|
y
2
|
|
x
1
−
x
2
|
≤
max
{
|
x
1
|
,
|
y
2
|
}
(
|
x
1
−
x
2
|
+
|
y
1
−
y
2
|
)
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
=
|
x
1
y
1
−
x
2
y
2
|
=
|
x
1
y
1
−
x
1
y
2
+
x
1
y
2
−
x
2
y
2
|
≤
|
x
1
|
|
y
1
−
y
2
|
+
|
y
2
|
|
x
1
−
x
2
|
≤
max
{
|
x
1
|
,
|
y
2
|
}
(
|
x
1
−
x
2
|
+
|
y
1
−
y
2
|
)
{:[|f(x_(1)”,”y_(1))-f(x_(2)”,”y_(2))|=|x_(1)y_(1)-x_(2)y_(2)|],[=|x_(1)y_(1)-x_(1)y_(2)+x_(1)y_(2)-x_(2)y_(2)|],[ <= |x_(1)||y_(1)-y_(2)|+|y_(2)||x_(1)-x_(2)|],[ <= max{|x_(1)|”,”|y_(2)|}(|x_(1)-x_(2)|+|y_(1)-y_(2)|)]:} \begin{align*}
|f(x_1, y_1) – f(x_2, y_2)| &= |x_1y_1 – x_2y_2| \\
&= |x_1y_1 – x_1y_2 + x_1y_2 – x_2y_2| \\
&\leq |x_1||y_1 – y_2| + |y_2||x_1 – x_2| \\
&\leq \max\{|x_1|, |y_2|\}(|x_1 – x_2| + |y_1 – y_2|)
\end{align*} | f ( x 1 , y 1 ) − f ( x 2 , y 2 ) | = | x 1 y 1 − x 2 y 2 | = | x 1 y 1 − x 1 y 2 + x 1 y 2 − x 2 y 2 | ≤ | x 1 | | y 1 − y 2 | + | y 2 | | x 1 − x 2 | ≤ max { | x 1 | , | y 2 | } ( | x 1 − x 2 | + | y 1 − y 2 | )
Since
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
c
≤
y
≤
d
c
≤
y
≤
d
c <= y <= d c \leq y \leq d c ≤ y ≤ d , we can take
L
=
max
{
|
a
|
,
|
b
|
,
|
c
|
,
|
d
|
}
L
=
max
{
|
a
|
,
|
b
|
,
|
c
|
,
|
d
|
}
L=max{|a|,|b|,|c|,|d|} L = \max\{|a|, |b|, |c|, |d|\} L = max { | a | , | b | , | c | , | d | } . Then,
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
≤
L
(
|
x
1
−
x
2
|
+
|
y
1
−
y
2
|
)
≤
L
2
(
x
1
−
x
2
)
2
+
(
y
1
−
y
2
)
2
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
≤
L
(
|
x
1
−
x
2
|
+
|
y
1
−
y
2
|
)
≤
L
2
(
x
1
−
x
2
)
2
+
(
y
1
−
y
2
)
2
|f(x_(1),y_(1))-f(x_(2),y_(2))| <= L(|x_(1)-x_(2)|+|y_(1)-y_(2)|) <= Lsqrt2sqrt((x_(1)-x_(2))^(2)+(y_(1)-y_(2))^(2)) |f(x_1, y_1) – f(x_2, y_2)| \leq L(|x_1 – x_2| + |y_1 – y_2|) \leq L\sqrt{2}\sqrt{(x_1 – x_2)^2 + (y_1 – y_2)^2} | f ( x 1 , y 1 ) − f ( x 2 , y 2 ) | ≤ L ( | x 1 − x 2 | + | y 1 − y 2 | ) ≤ L 2 ( x 1 − x 2 ) 2 + ( y 1 − y 2 ) 2
So,
f
(
x
,
y
)
=
x
y
f
(
x
,
y
)
=
x
y
f(x,y)=xy f(x, y) = xy f ( x , y ) = x y satisfies a Lipschitz condition on any rectangle
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
c
≤
y
≤
d
c
≤
y
≤
d
c <= y <= d c \leq y \leq d c ≤ y ≤ d with Lipschitz constant
L
2
L
2
Lsqrt2 L\sqrt{2} L 2 .
ii)
On a strip
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
−
∞
<
y
<
∞
−
∞
<
y
<
∞
-oo < y < oo -\infty < y < \infty − ∞ < y < ∞ :
Using a similar argument as in part (i), we can show that
f
(
x
,
y
)
=
x
y
f
(
x
,
y
)
=
x
y
f(x,y)=xy f(x, y) = xy f ( x , y ) = x y satisfies a Lipschitz condition on any strip
a
≤
x
≤
b
a
≤
x
≤
b
a <= x <= b a \leq x \leq b a ≤ x ≤ b and
−
∞
<
y
<
∞
−
∞
<
y
<
∞
-oo < y < oo -\infty < y < \infty − ∞ < y < ∞ with a Lipschitz constant
L
=
max
{
|
a
|
,
|
b
|
}
L
=
max
{
|
a
|
,
|
b
|
}
L=max{|a|,|b|} L = \max\{|a|, |b|\} L = max { | a | , | b | } .
iii) On the entire plane:
To show that
f
(
x
,
y
)
=
x
y
f
(
x
,
y
)
=
x
y
f(x,y)=xy f(x, y) = xy f ( x , y ) = x y does not satisfy a Lipschitz condition on the entire plane, consider the points
(
x
1
,
y
1
)
=
(
1
,
n
)
(
x
1
,
y
1
)
=
(
1
,
n
)
(x_(1),y_(1))=(1,n) (x_1, y_1) = (1, n) ( x 1 , y 1 ) = ( 1 , n ) and
(
x
2
,
y
2
)
=
(
0
,
0
)
(
x
2
,
y
2
)
=
(
0
,
0
)
(x_(2),y_(2))=(0,0) (x_2, y_2) = (0, 0) ( x 2 , y 2 ) = ( 0 , 0 ) for some large
n
∈
N
n
∈
N
n inN n \in \mathbf{N} n ∈ N . Then,
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
=
|
1
⋅
n
−
0
⋅
0
|
=
n
|
f
(
x
1
,
y
1
)
−
f
(
x
2
,
y
2
)
|
=
|
1
⋅
n
−
0
⋅
0
|
=
n
|f(x_(1),y_(1))-f(x_(2),y_(2))|=|1*n-0*0|=n |f(x_1, y_1) – f(x_2, y_2)| = |1 \cdot n – 0 \cdot 0| = n | f ( x 1 , y 1 ) − f ( x 2 , y 2 ) | = | 1 ⋅ n − 0 ⋅ 0 | = n
However,
(
x
1
−
x
2
)
2
+
(
y
1
−
y
2
)
2
=
1
2
+
n
2
≈
n
(
x
1
−
x
2
)
2
+
(
y
1
−
y
2
)
2
=
1
2
+
n
2
≈
n
sqrt((x_(1)-x_(2))^(2)+(y_(1)-y_(2))^(2))=sqrt(1^(2)+n^(2))~~n \sqrt{(x_1 – x_2)^2 + (y_1 – y_2)^2} = \sqrt{1^2 + n^2} \approx n ( x 1 − x 2 ) 2 + ( y 1 − y 2 ) 2 = 1 2 + n 2 ≈ n
for large
n
n
n n n . If
f
f
f f f were Lipschitz on the entire plane, there would exist a constant
L
L
L L L such that
n
≤
L
⋅
n
n
≤
L
⋅
n
n <= L*n n \leq L \cdot n n ≤ L ⋅ n for all
n
n
n n n , which is impossible. Therefore,
f
(
x
,
y
)
=
x
y
f
(
x
,
y
)
=
x
y
f(x,y)=xy f(x, y) = xy f ( x , y ) = x y does not satisfy a Lipschitz condition on the entire plane.
b) Use Frobenious method to find the series solution about
x
=
0
x
=
0
x=0 x=0 x = 0 of the equation
x
(
1
−
x
)
d
2
y
d
x
2
−
(
1
+
3
x
)
d
y
d
x
−
y
=
0
.
x
(
1
−
x
)
d
2
y
d
x
2
−
(
1
+
3
x
)
d
y
d
x
−
y
=
0
.
x(1-x)(d^(2)y)/(dx^(2))-(1+3x)(dy)/(dx)-y=0. x(1-x) \frac{d^2 y}{d x^2}-(1+3 x) \frac{d y}{d x}-y=0 . x ( 1 − x ) d 2 y d x 2 − ( 1 + 3 x ) d y d x − y = 0 .
Answer:
To solve the differential equation using the Frobenius method, we assume a solution of the form:
y
=
∑
n
=
0
∞
a
n
x
n
+
r
y
=
∑
n
=
0
∞
a
n
x
n
+
r
y=sum_(n=0)^(oo)a_(n)x^(n+r) y = \sum_{n=0}^{\infty} a_n x^{n+r} y = ∑ n = 0 ∞ a n x n + r
where
r
r
r r r is a constant to be determined. We then substitute this series into the differential equation and solve for the coefficients
a
n
a
n
a_(n) a_n a n .
First, we calculate the derivatives:
d
y
d
x
=
∑
n
=
0
∞
(
n
+
r
)
a
n
x
n
+
r
−
1
d
y
d
x
=
∑
n
=
0
∞
(
n
+
r
)
a
n
x
n
+
r
−
1
(dy)/(dx)=sum_(n=0)^(oo)(n+r)a_(n)x^(n+r-1) \frac{dy}{dx} = \sum_{n=0}^{\infty} (n+r) a_n x^{n+r-1} d y d x = ∑ n = 0 ∞ ( n + r ) a n x n + r − 1
d
2
y
d
x
2
=
∑
n
=
0
∞
(
n
+
r
)
(
n
+
r
−
1
)
a
n
x
n
+
r
−
2
d
2
y
d
x
2
=
∑
n
=
0
∞
(
n
+
r
)
(
n
+
r
−
1
)
a
n
x
n
+
r
−
2
(d^(2)y)/(dx^(2))=sum_(n=0)^(oo)(n+r)(n+r-1)a_(n)x^(n+r-2) \frac{d^2y}{dx^2} = \sum_{n=0}^{\infty} (n+r)(n+r-1) a_n x^{n+r-2} d 2 y d x 2 = ∑ n = 0 ∞ ( n + r ) ( n + r − 1 ) a n x n + r − 2
Substituting these into the differential equation, we get:
x
(
1
−
x
)
∑
n
=
0
∞
(
n
+
r
)
(
n
+
r
−
1
)
a
n
x
n
+
r
−
2
−
(
1
+
3
x
)
∑
n
=
0
∞
(
n
+
r
)
a
n
x
n
+
r
−
1
−
∑
n
=
0
∞
a
n
x
n
+
r
=
0
x
(
1
−
x
)
∑
n
=
0
∞
(
n
+
r
)
(
n
+
r
−
1
)
a
n
x
n
+
r
−
2
−
(
1
+
3
x
)
∑
n
=
0
∞
(
n
+
r
)
a
n
x
n
+
r
−
1
−
∑
n
=
0
∞
a
n
x
n
+
r
=
0
x(1-x)sum_(n=0)^(oo)(n+r)(n+r-1)a_(n)x^(n+r-2)-(1+3x)sum_(n=0)^(oo)(n+r)a_(n)x^(n+r-1)-sum_(n=0)^(oo)a_(n)x^(n+r)=0 x(1-x) \sum_{n=0}^{\infty} (n+r)(n+r-1) a_n x^{n+r-2} – (1+3x) \sum_{n=0}^{\infty} (n+r) a_n x^{n+r-1} – \sum_{n=0}^{\infty} a_n x^{n+r} = 0 x ( 1 − x ) ∑ n = 0 ∞ ( n + r ) ( n + r − 1 ) a n x n + r − 2 − ( 1 + 3 x ) ∑ n = 0 ∞ ( n + r ) a n x n + r − 1 − ∑ n = 0 ∞ a n x n + r = 0
Expanding and combining like terms, we have:
∑
n
=
0
∞
[
(
n
+
r
)
(
n
+
r
−
1
)
−
(
n
+
r
)
+
1
]
a
n
x
n
+
r
−
∑
n
=
0
∞
[
3
(
n
+
r
)
+
(
n
+
r
)
(
n
+
r
−
1
)
]
a
n
x
n
+
r
+
1
=
0
∑
n
=
0
∞
[
(
n
+
r
)
(
n
+
r
−
1
)
−
(
n
+
r
)
+
1
]
a
n
x
n
+
r
−
∑
n
=
0
∞
[
3
(
n
+
r
)
+
(
n
+
r
)
(
n
+
r
−
1
)
]
a
n
x
n
+
r
+
1
=
0
sum_(n=0)^(oo)[(n+r)(n+r-1)-(n+r)+1]a_(n)x^(n+r)-sum_(n=0)^(oo)[3(n+r)+(n+r)(n+r-1)]a_(n)x^(n+r+1)=0 \sum_{n=0}^{\infty} [(n+r)(n+r-1) – (n+r) + 1] a_n x^{n+r} – \sum_{n=0}^{\infty} [3(n+r) + (n+r)(n+r-1)] a_n x^{n+r+1} = 0 ∑ n = 0 ∞ [ ( n + r ) ( n + r − 1 ) − ( n + r ) + 1 ] a n x n + r − ∑ n = 0 ∞ [ 3 ( n + r ) + ( n + r ) ( n + r − 1 ) ] a n x n + r + 1 = 0
Equating coefficients of
x
n
+
r
x
n
+
r
x^(n+r) x^{n+r} x n + r and
x
n
+
r
+
1
x
n
+
r
+
1
x^(n+r+1) x^{n+r+1} x n + r + 1 to zero, we get the recurrence relations:
(
n
+
r
)
(
n
+
r
−
2
)
a
n
−
(
3
(
n
+
r
)
+
(
n
+
r
)
(
n
+
r
−
1
)
)
a
n
+
1
=
0
(
n
+
r
)
(
n
+
r
−
2
)
a
n
−
(
3
(
n
+
r
)
+
(
n
+
r
)
(
n
+
r
−
1
)
)
a
n
+
1
=
0
(n+r)(n+r-2)a_(n)-(3(n+r)+(n+r)(n+r-1))a_(n+1)=0 (n+r)(n+r-2) a_n – (3(n+r) + (n+r)(n+r-1)) a_{n+1} = 0 ( n + r ) ( n + r − 2 ) a n − ( 3 ( n + r ) + ( n + r ) ( n + r − 1 ) ) a n + 1 = 0
Simplifying, we find:
(
n
+
r
)
(
n
+
r
−
2
)
a
n
−
(
n
+
r
+
1
)
(
n
+
r
+
3
)
a
n
+
1
=
0
(
n
+
r
)
(
n
+
r
−
2
)
a
n
−
(
n
+
r
+
1
)
(
n
+
r
+
3
)
a
n
+
1
=
0
(n+r)(n+r-2)a_(n)-(n+r+1)(n+r+3)a_(n+1)=0 (n+r)(n+r-2) a_n – (n+r+1)(n+r+3) a_{n+1} = 0 ( n + r ) ( n + r − 2 ) a n − ( n + r + 1 ) ( n + r + 3 ) a n + 1 = 0
For
n
=
0
n
=
0
n=0 n = 0 n = 0 , we have the indicial equation:
r
(
r
−
2
)
=
0
r
(
r
−
2
)
=
0
r(r-2)=0 r(r-2) = 0 r ( r − 2 ) = 0
which gives
r
=
0
r
=
0
r=0 r = 0 r = 0 or
r
=
2
r
=
2
r=2 r = 2 r = 2 .
For
r
=
0
r
=
0
r=0 r = 0 r = 0 , the recurrence relation becomes:
n
(
n
−
2
)
a
n
−
(
n
+
1
)
(
n
+
3
)
a
n
+
1
=
0
n
(
n
−
2
)
a
n
−
(
n
+
1
)
(
n
+
3
)
a
n
+
1
=
0
n(n-2)a_(n)-(n+1)(n+3)a_(n+1)=0 n(n-2) a_n – (n+1)(n+3) a_{n+1} = 0 n ( n − 2 ) a n − ( n + 1 ) ( n + 3 ) a n + 1 = 0
or
a
n
+
1
=
n
(
n
−
2
)
(
n
+
1
)
(
n
+
3
)
a
n
a
n
+
1
=
n
(
n
−
2
)
(
n
+
1
)
(
n
+
3
)
a
n
a_(n+1)=(n(n-2))/((n+1)(n+3))a_(n) a_{n+1} = \frac{n(n-2)}{(n+1)(n+3)} a_n a n + 1 = n ( n − 2 ) ( n + 1 ) ( n + 3 ) a n
Since
a
0
a
0
a_(0) a_0 a 0 is arbitrary, let’s choose
a
0
=
1
a
0
=
1
a_(0)=1 a_0 = 1 a 0 = 1 for simplicity. Then, we can find the next few coefficients:
For
n
=
0
n
=
0
n=0 n = 0 n = 0 :
a
1
=
0
(
0
−
2
)
(
0
+
1
)
(
0
+
3
)
a
0
=
0
a
1
=
0
(
0
−
2
)
(
0
+
1
)
(
0
+
3
)
a
0
=
0
a_(1)=(0(0-2))/((0+1)(0+3))a_(0)=0 a_1 = \frac{0(0-2)}{(0+1)(0+3)} a_0 = 0 a 1 = 0 ( 0 − 2 ) ( 0 + 1 ) ( 0 + 3 ) a 0 = 0
For
n
=
1
n
=
1
n=1 n = 1 n = 1 :
a
2
=
1
(
1
−
2
)
(
1
+
1
)
(
1
+
3
)
a
1
=
0
a
2
=
1
(
1
−
2
)
(
1
+
1
)
(
1
+
3
)
a
1
=
0
a_(2)=(1(1-2))/((1+1)(1+3))a_(1)=0 a_2 = \frac{1(1-2)}{(1+1)(1+3)} a_1 = 0 a 2 = 1 ( 1 − 2 ) ( 1 + 1 ) ( 1 + 3 ) a 1 = 0
For
n
=
2
n
=
2
n=2 n = 2 n = 2 :
a
3
=
2
(
2
−
2
)
(
2
+
1
)
(
2
+
3
)
a
2
=
0
a
3
=
2
(
2
−
2
)
(
2
+
1
)
(
2
+
3
)
a
2
=
0
a_(3)=(2(2-2))/((2+1)(2+3))a_(2)=0 a_3 = \frac{2(2-2)}{(2+1)(2+3)} a_2 = 0 a 3 = 2 ( 2 − 2 ) ( 2 + 1 ) ( 2 + 3 ) a 2 = 0
For
n
=
3
n
=
3
n=3 n = 3 n = 3 :
a
4
=
3
(
3
−
2
)
(
3
+
1
)
(
3
+
3
)
a
3
=
0
a
4
=
3
(
3
−
2
)
(
3
+
1
)
(
3
+
3
)
a
3
=
0
a_(4)=(3(3-2))/((3+1)(3+3))a_(3)=0 a_4 = \frac{3(3-2)}{(3+1)(3+3)} a_3 = 0 a 4 = 3 ( 3 − 2 ) ( 3 + 1 ) ( 3 + 3 ) a 3 = 0
And so on. It appears that all coefficients after
a
0
a
0
a_(0) a_0 a 0 are zero. Therefore, the solution for
r
=
0
r
=
0
r=0 r = 0 r = 0 is:
y
=
a
0
=
1
y
=
a
0
=
1
y=a_(0)=1 y = a_0 = 1 y = a 0 = 1
Now, let’s consider the case
r
=
2
r
=
2
r=2 r = 2 r = 2 :
For
r
=
2
r
=
2
r=2 r = 2 r = 2 , the recurrence relation becomes:
(
n
+
2
)
(
n
)
a
n
−
(
n
+
3
)
(
n
+
5
)
a
n
+
1
=
0
(
n
+
2
)
(
n
)
a
n
−
(
n
+
3
)
(
n
+
5
)
a
n
+
1
=
0
(n+2)(n)a_(n)-(n+3)(n+5)a_(n+1)=0 (n+2)(n) a_n – (n+3)(n+5) a_{n+1} = 0 ( n + 2 ) ( n ) a n − ( n + 3 ) ( n + 5 ) a n + 1 = 0
or
a
n
+
1
=
(
n
+
2
)
(
n
)
(
n
+
3
)
(
n
+
5
)
a
n
a
n
+
1
=
(
n
+
2
)
(
n
)
(
n
+
3
)
(
n
+
5
)
a
n
a_(n+1)=((n+2)(n))/((n+3)(n+5))a_(n) a_{n+1} = \frac{(n+2)(n)}{(n+3)(n+5)} a_n a n + 1 = ( n + 2 ) ( n ) ( n + 3 ) ( n + 5 ) a n
Again, let’s choose
a
0
=
1
a
0
=
1
a_(0)=1 a_0 = 1 a 0 = 1 . Then, we can find the next few coefficients:
For
n
=
0
n
=
0
n=0 n = 0 n = 0 :
a
1
=
2
(
0
)
(
0
+
3
)
(
0
+
5
)
a
0
=
0
a
1
=
2
(
0
)
(
0
+
3
)
(
0
+
5
)
a
0
=
0
a_(1)=(2(0))/((0+3)(0+5))a_(0)=0 a_1 = \frac{2(0)}{(0+3)(0+5)} a_0 = 0 a 1 = 2 ( 0 ) ( 0 + 3 ) ( 0 + 5 ) a 0 = 0
For
n
=
1
n
=
1
n=1 n = 1 n = 1 :
a
2
=
3
(
1
)
(
1
+
3
)
(
1
+
5
)
a
1
=
0
a
2
=
3
(
1
)
(
1
+
3
)
(
1
+
5
)
a
1
=
0
a_(2)=(3(1))/((1+3)(1+5))a_(1)=0 a_2 = \frac{3(1)}{(1+3)(1+5)} a_1 = 0 a 2 = 3 ( 1 ) ( 1 + 3 ) ( 1 + 5 ) a 1 = 0
And so on. It appears that all coefficients after
a
0
a
0
a_(0) a_0 a 0 are also zero in this case. Therefore, the solution for
r
=
2
r
=
2
r=2 r = 2 r = 2 is:
y
=
a
0
x
2
=
x
2
y
=
a
0
x
2
=
x
2
y=a_(0)x^(2)=x^(2) y = a_0 x^2 = x^2 y = a 0 x 2 = x 2
In conclusion, the series solutions about
x
=
0
x
=
0
x=0 x=0 x = 0 of the equation
x
(
1
−
x
)
d
2
y
d
x
2
−
(
1
+
3
x
)
d
y
d
x
−
y
=
0
x
(
1
−
x
)
d
2
y
d
x
2
−
(
1
+
3
x
)
d
y
d
x
−
y
=
0
x(1-x)(d^(2)y)/(dx^(2))-(1+3x)(dy)/(dx)-y=0 x(1-x) \frac{d^2 y}{d x^2}-(1+3 x) \frac{d y}{d x}-y=0 x ( 1 − x ) d 2 y d x 2 − ( 1 + 3 x ) d y d x − y = 0 are
y
=
1
y
=
1
y=1 y = 1 y = 1 and
y
=
x
2
y
=
x
2
y=x^(2) y = x^2 y = x 2 .